An Inquiry on the Legal Status and Protection of Climate Refugees from an International Law Perspective - Alican Candoğan; Mehmet Botan Kayhan (İstanbul Hukuk Mecmuası)
Climate crisis-related displacement is one of the most prominent issues in our world. Although, there is no given legal definition for climate refugees in any international legal convention, in order to analyse this phenomenon; those who are compelled to leave their homes due to climate change-related catastrophes would be accepted as climate refugees within this article. It is clear that climate refugees, who sit at the crossroads of climate change and the refugee crises, can only be adequately protected through a combination of climate action and refugee rights. The climate crisis is a substructure of the refugee crisis. Therefore, climate action, which is principally aimed at solving substructural problems, is essential for solving the superstructural climate refugee crisis. Nevertheless, according to scientific predictions, even the most optimistic scenarios foresee a considerable change in the climate. Hence, even the most optimistic scenarios in which humanity takes climate action may not be enough to prevent the existence of climate refugees. The Refugee Convention Relating to the Status of Refugees, which is currently the most prominent international convention on refugee rights, does not encompass climate refugees because of its contingent wording. Thus, it is necessary to adopt comprehensive legislation that protects the rights of climate refugees in addition to climate action that would reduce the number of possible refugees. Yet both substructural and superstructural issues are in a position of conundrum due to the extant international political and legal system, which prioritises the national sovereignty and states consents. Consequently, legal solutions in the sense of both climate and refugee crises fall short if the international political and legal status quo is ignored.